Implementasi Corporate Governance Dan Peningkatan Kinerja Perusahaan - Syamsudin Syamsudin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2011)
Article describes the benefits of corporate governance, with the implementation of good corporate governance will improve the performance of the company, so the owner will get a return on investment. Good corporate governance will reduce risk, improve profits and firm value